Effect of time and temperature on butanol production from palm oil mill effluent (POME) by anaerobic fermentation using clostridium beijerinckii - Siti Hazriah, Hamzah (2010)
Owing to the increasing volume of palm oil mill effluent (POME) wastewater generated, disposal remains as perennial problem and its bioconversion has been considered as an option for pollution control (C.N. Hipolito et al., 2008). Thus, the availability of an inexpensive raw material; POME which will used in this research is essential if solvent fermentation is to become economically viable. In Malaysia, POME represents an alternative cheap carbon source for fermentation processes that is attractive in both economic and geographical considerations. The mainly research purpose is to study the production of butanol from the anareobic fermentation of solventogenic bacteria (clostridium beijerinkii, ATCC 51743) by using POME as the fermentation media. The scope of the research is to study the effect of fermentation time and temperature to the butanol production. The fermentation is based on batch fermentation in schott bottle. It is an anaerobic fermentation and the strain, Clostridium Beijerinckii (ATCC 51743) was treated strictly in an anaerobic condition. Optimum conditions that were maintained in this research are the substrate concentration and agitation rate. POME and Reinforced Clostridia Media (RCM) were used as the growth medium in this batch culture. The fermentation temperature that were used in this study are 35°C, 40°C and 45°C while the fermentation time that were used are 48 to 72 hours respectively. The results indicated that the concentration of butanol will decreases as the temperature increases. The highest concentration of butanol that produced by POME was 0.224 g Lat 35°C by 72 hours of fermentation. From this study, it is showed that POME can produce butanol at optimum fermentation temperature at 35°C in 72 hours of fermentation time. Hence, the result also showed that POME is viable to use as growth medium to produce butanol.